2012
DOI: 10.3997/2214-4609.20148704
|View full text |Cite
|
Sign up to set email alerts
|

Building Detailed Structurally Conformable Velocity Models with High Definition Tomography

Abstract: Velocity model building remains a crucial step in seismic depth imaging. A general drawback of conventional tomographic approaches is that the estimated velocity models do not conform enough to structures. We present several applications of an innovative high resolution tomography that inverts densely picked residual move-out data to reveal detailed structurally conformable velocities. The application to the synthetic 2D Marmousi II dataset offers the possibility to carefully assess the method. It demonstrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…After dip and RMO picking, a first step of velocity model building was performed for time and depth using non-linear slope tomography (Guillaume et al, 2008;Depagne et al, 2012) as shown below (left image in Figure 4). A second step of velocity model building using high-definition tomography (Guillaume et al, 2012) resulted in an accurate high-resolution velocity model that conforms nicely to the structure (right in Figure 4). Up and Down gathers were migrated with the updated velocity model which produced CIGs with improved flattening (Figure 3).…”
Section: Brunei 2d Variable-depth Streamer Acquisition Real Data Casementioning
confidence: 97%
“…After dip and RMO picking, a first step of velocity model building was performed for time and depth using non-linear slope tomography (Guillaume et al, 2008;Depagne et al, 2012) as shown below (left image in Figure 4). A second step of velocity model building using high-definition tomography (Guillaume et al, 2012) resulted in an accurate high-resolution velocity model that conforms nicely to the structure (right in Figure 4). Up and Down gathers were migrated with the updated velocity model which produced CIGs with improved flattening (Figure 3).…”
Section: Brunei 2d Variable-depth Streamer Acquisition Real Data Casementioning
confidence: 97%
“…A good initial model is important. The high definition tomography (Guillaume et al, 2012) and conventional low frequency FWI can be used to build the initial model for our approach.…”
Section: Applicationsmentioning
confidence: 99%
“…The first one allows sharp, geologically-consistent, velocity contrasts in the velocity model (multi-layer non-linear slope tomography proposed by Guillaume et al (2013)), the second one uses dense volumetric picking (high definition tomography proposed by Guillaume et al (2012)). The introduction of sharp contrasts in the velocity model as well as the conversion of dense residual moveout information into a high-resolution structurally conformant velocity model greatly enhance the vertical resolution and the relevance of velocity for reservoir characterization.…”
Section: Filling the Mid-frequency Gap With Ray-based Tomographymentioning
confidence: 99%